2022
DOI: 10.1097/aln.0000000000004439
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Postoperative Cognitive Dysfunction by Minocycline in Elderly Patients after Total Knee Arthroplasty: A Randomized, Double-blind, Placebo-controlled Clinical Trial

Abstract: Background There are no effective pharmacologic interventions for preventing postoperative cognitive dysfunction in daily practice. Since the antibiotic minocycline is known to suppress postoperative neuroinflammation, this study hypothesized and investigated whether minocycline might have a preventive effect on postoperative cognitive dysfunction after noncardiac surgery. Methods This study included patients aged more than 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…A series of specific and potent anti-inflammatory therapeutic drugs and methods have been identified and developed, including specific pro-resolving inflammatory mediators (such as Maresin 1 [ 39 ]) and cholinergic agonists (such as nicotine [ 40 ]). Despite extensive basic research exploring various small molecule neuroprotective agents and approaches targeting inflammation for the prevention and treatment of POCD over the past few decades, the clinical translation progress has been slow [ 35 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A series of specific and potent anti-inflammatory therapeutic drugs and methods have been identified and developed, including specific pro-resolving inflammatory mediators (such as Maresin 1 [ 39 ]) and cholinergic agonists (such as nicotine [ 40 ]). Despite extensive basic research exploring various small molecule neuroprotective agents and approaches targeting inflammation for the prevention and treatment of POCD over the past few decades, the clinical translation progress has been slow [ 35 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its anti-inflammatory properties, multiple reports have focused on minocycline’s therapeutic effect on cognitive dysfunction. However, in 2023, Takazawa et al examined minocycline’s effect on POCD in elderly individuals administered total knee arthroplasty and found that 200 mg of minocycline daily from the day before surgery until the seventh day after surgery did not decrease POCD incidence, contradicting many preclinical studies [ 51 ]. The negative results of this study may be related to the short dosing period.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroprotective benefits and reduced cognitive impairment induced by sepsis or surgery have been observed when microglia activation is prevented using the antibiotic minocycline ( Michels et al, 2015 ; Tan et al, 2023 ). Unfortunately, minocycline failed to prevent postoperative cognitive dysfunction in a recent clinical trial, suggesting that the mechanisms underlying neuroinflammation-related brain dysfunction extend well beyond microglial activation ( Takazawa et al, 2023 ).…”
Section: M1 Microglia As the Primary Source Of Brain Il-1β During Sepsismentioning
confidence: 99%